2021
DOI: 10.1111/ene.15030
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis is associated with higher comorbidity and health care resource use: A population‐based, case–control study in a western Mediterranean region

Abstract: Background and purpose: Comorbidities are common in multiple sclerosis (MS), and have been associated with worse outcomes and increased health care resource usage. We studied the frequency of comorbidities and adverse health behaviors (AHBs) in MS patients in the Mediterranean region of Catalonia.Methods: This population-based, case-control study used primary health care information covering 80% of Catalonia's population. Cases were matched by age/sex with randomly chosen controls (ratio = 1:5). Demographic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
(124 reference statements)
1
1
0
Order By: Relevance
“…In our study, we found that the prevalence of stroke is higher in PwMS than in the general population irrespective of sex and age, in line with the literature [ 30 , 31 ]. The risk of developing cerebrovascular disease has been evaluated in PwMS and, although there are discordant findings [ 32 ], it seems that there is an increased risk of stroke especially in the years immediately following the diagnosis of MS [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found that the prevalence of stroke is higher in PwMS than in the general population irrespective of sex and age, in line with the literature [ 30 , 31 ]. The risk of developing cerebrovascular disease has been evaluated in PwMS and, although there are discordant findings [ 32 ], it seems that there is an increased risk of stroke especially in the years immediately following the diagnosis of MS [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…A frequent problem in previous studies is which costs should be attributed to MS. One important finding is that oncological therapies were among the most expensive drugs, even in this relatively young patient cohort. A recent community‐based study from Spain found an increased risk for stroke, epilepsy, bipolar disorder, and depression among MS patients (Cardenas‐Robledo et al., 2021 ), underlining the need to consider care and costs other than those directly attributed to MS.…”
Section: Discussionmentioning
confidence: 99%